Demonstration of solids-associated virus in wastewater and sludge. - Wellings, F M (1976)
Data presented demonstrate the relatively high multiplicity of solids-associated virus in field samples, i.e., wastewater, sludge, and soils. Influent, effluent, and chlorinated effluent samples showed 16.1 to 100% of the total virus demonstrated in samples to be solids associated. Three techniques for freeing solids-associated virus are described and compared. Using sonication of solids and polyethylene glycol concentration, virus was demonstrated in fully digested sludge (60 days at 34 C), sand at the site of a sewer leak, and dried sludge cake and mud 900 m downstream from a sewage disposal site. These data emphasize the inadequacy of virus concentration techniques that do not include the processing of solids. In situ elution failed to free solids-associated virus.